EP 116. Impact of Rhodiola Rosea extract WS1375 on electrophysiological correlates of attention allocation in a dual task paradigm. Issue 9 (September 2016) - Heldmann, M.; Roth, G.; Dienel, A.; Münte, T.F.
Abstract : There is some evidence that Rhodiola Rosea has a beneficial influence on higher cognitive functions. In an open label, single-arm study the impact of Rhodiola Rosea on the allocation of different attention resources and complex attentional parameters was investigated. Fifty healthy participants (age range 30–50 yrs.) received Rhodiola Rosea extractWS® 1375 (200 mg) for twelve weeks twice a day. Neuropsychological assessment and recording of event-related potentials at the onset of the study, after 6 and after 12 weeks were used to determine the potential effect of Rhodiola Rosea on higher cognitive functions. ERPs were recorded in a dual task paradigm comprising a visual search task and a syllable discrimination task. Across time a significant increase in the amplitude of the P300 component, a component known to indicate the amount of available attentional resources, was observed. At the behavioral level, participants became faster and performed the dual-task more accurate. This result was confirmed by outcomes from the attentional network task (ANT) were subjects showed an increase in performance speed while being less vulnerable to interference effects, and the findings from a GoNogo and a divided attention task, revealing shorter reaction times and increased performance accuracy across time. Based on these results, we conclude that Rhodiola Rosea has a beneficial effect on the allocation of attentional resources, performance speed and task accuracy in situations with high attentional demands. However, future investigations have to investigate the potential influence of repetition effects on the presented results.